Problematika Kurangnya Media Pembelajaran Di SD Tanjungsari Yang Berdampak Pada Ketidak Efektifan Pada Proses Penilaian - Qomariyah, Ryzca Siti; Karimah, Inayatul; Masruro, Masruro; Soleha, Rita Soleha; ,, Dandi Ferdiansyah (CV. ITTC INDONESIA, 2022)
Learning media is a means of influencing a teaching and learning process. In the absence of learning media, it is difficult for KBM to be implemented effectively. Without realizing it, learning media has an important role in addition to teachers and students as the main objects in the learning process. In this case it can be concluded that if the learning media is minimal/less then it will hinder the creation of real educational goals. Besides that, the full contribution of the school is also very much needed in creating competent teachers in order to be able to form a conducive and enjoyable student learning enthusiasm that can get encouragement in increasing student motivation in learning. The effectiveness of the assessment is also necessary in the teaching and learning process, because with the assessment the teacher can determine the abilities of each individual/student. Assessment does not only focus on the learning outcomes that have been obtained, but also on the process of how students learn. Assessment also functions as a relationship that influences each other and there is reciprocity between students and teachers, assessment in education also aims to find out the increase in student learning activities, in order to improve and enhance student learning at school and at home. Problems that often occur related to learning media usually occur in schools located in remote areas, which are far from the reach of the government. It can be exemplified by the lack of supply of textbooks and infrastructure such as projectors, etc. that can support success in learning. In this case students have difficulty finding learning resources, so the teacher must contribute to creating learning media to cover these deficiencies, because the teacher has a very big role in changing student learning.